2009
DOI: 10.1016/j.joca.2008.06.018
|View full text |Cite
|
Sign up to set email alerts
|

Joint inflammation increases glucosamine levels attained in synovial fluid following oral administration of glucosamine hydrochloride

Abstract: Synovial inflammation leads to significantly higher synovial glucosamine concentrations compared to levels attained in healthy joints following oral administration of glucosamine hydrochloride. Whether these higher levels are translated into a therapeutic effect on the joint tissues remains to be elucidated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
20
0
2

Year Published

2012
2012
2020
2020

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 27 publications
(25 citation statements)
references
References 30 publications
3
20
0
2
Order By: Relevance
“…It has been shown that supplemental glucosamine reaches the site of action, i.e., the joints and the synovial fluid [6][7][8][9][10][11]. Supplemental glucosamine can therefore be utilised by the cells to maintain the balance between the breakdown and synthesis in the form of dietary supplements).…”
Section: The Role Of Glucosamine In Joint Physiologymentioning
confidence: 99%
“…It has been shown that supplemental glucosamine reaches the site of action, i.e., the joints and the synovial fluid [6][7][8][9][10][11]. Supplemental glucosamine can therefore be utilised by the cells to maintain the balance between the breakdown and synthesis in the form of dietary supplements).…”
Section: The Role Of Glucosamine In Joint Physiologymentioning
confidence: 99%
“…The applicant also provided studies in animals on the effect of glucosamine on cartilage formation/degradation (Chen et al, 2010;Meulyzer et al, 2009;Naito et al, 2010;Oegema et al, 2002;Taniguchi et al, 2012). Four studies were provided in animal models of OA, i.e.…”
Section: Mechanistic Studiesmentioning
confidence: 99%
“…in rats and rabbits with OA induced surgically or enzymatically (Chen et al, 2010;Naito et al, 2010;Oegema et al, 2002) and in Hartley guinea pigs susceptible to spontaneous OA (Taniguchi et al, 2012). One study was provided on the effect of glucosamine on induced (by injection of lipopolysaccharides from E. coli) inflammation of joints in horses (Meulyzer et al, 2009). The applicant was invited to justify the validity of the animal models in the context of the claimed effect, i.e.…”
Section: Mechanistic Studiesmentioning
confidence: 99%
“…Chapter inflammation based in these studies will likely be in the range of 1-18 µM for both horses and humans and most in vitro studies showing benefits with glucosamine used considerably higher concentrations (Meulyzer et al 2009). in vitro studies to the in vivo situation by providing some prediction of fluid and tissue concentrations for GU and CS after oral dosing.…”
mentioning
confidence: 99%
“…The conclusion was that higher synovial fluid concentrations of glucosamine were achieved with glucosamine sulfate, but whether this difference translated into a therapeutic effect on the joint tissues remains to be elucidated (Meulyzer et al 2008). In a follow-up paper the same research group demonstrated that joint inflammation (induced with Escherichia coli lipopolysaccharide [LPS]) increases GU levels obtained in synovial fluid following oral administration of glucosamine hydrochloride up to fourfold higher than in the clinically normal joints suggested the possibility of an enhanced effect (as synovitis is important in the pathobiology of equine OA) (Meulyzer et al 2009). On the other hand, the maximal GU levels attainable in the synovial fluid in the presence of…”
mentioning
confidence: 99%